1991
DOI: 10.1161/01.str.22.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Sodium, ATP, and intracellular pH transients during reversible complete ischemia of dog cerebrum.

Abstract: We tested the hypotheses that with the onset of cerebral ischemia, massive cellular sodium influx does not occur until adenosine triphosphate is fully depleted and that on reperfusion, neuronal sodium efflux does not occur until adenosine triphosphate is fully restored. We examined the temporal relationships among transcellular sodium, energy metabolism, and intracellular pH with sodium and phosphorus magnetic resonance spectroscopy in a new, hemodynamically stable, brain stem-sparing model of reversible, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 47 publications
6
38
0
2
Order By: Relevance
“…Different from DHCA, clinical application of EPR in management of ExCA would only be feasible after a normothermic ExCA has occurred. Brain energy reserve is depleted B5 mins after normothermic CA (Shaffner et al, 1999;Eleff et al, 1991). Thus, to postpone energy failure, it may be important for preservation strategies to prevent energy depletion in brain and restore energy levels during induction of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Different from DHCA, clinical application of EPR in management of ExCA would only be feasible after a normothermic ExCA has occurred. Brain energy reserve is depleted B5 mins after normothermic CA (Shaffner et al, 1999;Eleff et al, 1991). Thus, to postpone energy failure, it may be important for preservation strategies to prevent energy depletion in brain and restore energy levels during induction of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen 32 has shown that the extracellular potassium concentration ([K + ] e ) changes by only a small amount during the 1-2 minutes following the onset of ischemia or anoxia, but that this is followed by a steep increase in [K + ] c as depolarization ensues. Both Eleff et al 33 and Pekar et al 34 have measured intracellular ATP and sodium by nuclear magnetic resonance (NMR) spectroscopy following complete ischemia. The observations reported by Pekar et al using both phosphorus-31 and multiple quantum-filtered sodium-23 NMR spectroscopy show that upon production of cerebral ischemia there is a delay of approximately 2 minutes before the ATP level begins to fall and that of intracellular sodium begins to increase.…”
Section: Figure 3 Scatterplot Of Signal Intensity Ratio (Sir) Determmentioning
confidence: 99%
“…3338 Eleff et al 33 have suggested that the initial phase after reperfusion consists of energy-driven sodium extrusion (and thus, presumably, accumulation of potassium), such that full ATP recovery is delayed until this process reaches a steady state, and this is then followed by normalization of intracellular pH. The rate of energy recovery following ischemia depends on the duration of ischemia.…”
Section: Figure 3 Scatterplot Of Signal Intensity Ratio (Sir) Determmentioning
confidence: 99%
“…A similar decrease of 11 ± 8% in sodium signal was detected in a rabbit model in a region which ultimately infarcted, although it was not possible to say whether this measured decrease was in core or penumbra tissue (28) . Further, a 13% decrease in sodium signal was detected in a spectroscopic study of a canine model, but again no discrimination between core and penumbra was possible (44) . Nevertheless, if verified in further studies, this decrease in sodium signal could help identify the presence of penumbra tissue in the acute phase, and hence a PWI-Na mismatch approach may be warranted, or indeed Na-MR imaging alone (27) .…”
Section: Pre-clinical Stroke Na-mri Studiesmentioning
confidence: 98%